2017
DOI: 10.1111/1462-2920.13726
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic adaptation of a laterally acquired pectin degradation pathway in marine gammaproteobacteria

Abstract: Summary Mobile genomic islands distribute functional traits between microbes and habitats, yet it remains unclear how their proteins adapt to new environments. Here we used a comparative phylogenomic and proteomic approach to show that the marine bacterium Pseudoalteromonas haloplanktis ANT/505 acquired a genomic island with a functional pathway for pectin catabolism. Bioinformatics and biochemical experiments revealed that this pathway encodes a series of carbohydrate‐active enzymes including two multi‐modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 65 publications
4
40
0
Order By: Relevance
“…The environmental importance of alginate is reflected by the occurrence of alginate lyases in various bacterial taxa [48]. Pectin, largely composed of α-(1-4)-galacturonate, is abundant in terrestrial plants, but the presence of complex pectinolytic operons in marine bacteria [49] and up to 0.3 µM galacturonate during phytoplankton blooms [50] suggest that pectinous substrates are common in marine systems as well. Due to their gelling capacities, alginate and pectin may also occur in transparent exopolymer particles [50,51].…”
Section: Introductionmentioning
confidence: 99%
“…The environmental importance of alginate is reflected by the occurrence of alginate lyases in various bacterial taxa [48]. Pectin, largely composed of α-(1-4)-galacturonate, is abundant in terrestrial plants, but the presence of complex pectinolytic operons in marine bacteria [49] and up to 0.3 µM galacturonate during phytoplankton blooms [50] suggest that pectinous substrates are common in marine systems as well. Due to their gelling capacities, alginate and pectin may also occur in transparent exopolymer particles [50,51].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the most abundant enzyme detected, i.e., the pectate lyase-like protein, was annotated as a hypothetical protein and only suggested here as a hydrolytic enzyme for polysaccharides based on a pectate lyase-like domain it contains. Other pectate lyases have been detected in marine microbes, but these seem to have been acquired from a terrestrial origin (Hehemann et al, 2017). Nevertheless, this is not the norm and most marine microbes have a novel array of untapped hydrolytic enzymes that largely differ from their well-known terrestrial counterparts (Hehemann et al, 2014), which require further characterization.…”
Section: Correlation Between Culture Growth and Exoproteomesmentioning
confidence: 99%
“…; Hehemann et al . ). The mechanism used to transfer GIs devoid of recombination and conjugation modules remains largely unexplored.…”
Section: Introductionmentioning
confidence: 97%
“…Marine Gammaproteobacteria, including Pseudoalteromonas, Alteromonas, Shewanella and Vibrio, are the genera that most commonly adopt a particle-associated lifestyle in marine environments (Garcia-Martinez et al, 2002;Mai-Prochnow et al, 2006;Mahmoud, 2015). Comparative genomics has shown that these species often contain similar mobile genetic elements and that many of these species cohabit in the same microniches, e.g., marine biofilms (Daccord et al, 2013;Hehemann et al, 2017). The spread of mobile genetic elements by horizontal gene transfer is more frequent in biofilms than in free-living bacteria (Hausner and Wuertz, 1999;Sorensen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation